2015
DOI: 10.6007/ijarbss/v5-i3/1522
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Corporate Social Responsibility Dimensions on Employee Engagement in Iran

Abstract: The opening is necessary, but not sufficient, it helps provide remedial opportunities for developing countries by providing the means for poor countries to get out of underdevelopment, but on the other hand it makes them incur costs and risks. Our study conducted for the case of Tunisia showed that the opening will increase inequality, if it is not accompanied by control policies against disparities. This paper shows that the Atkinson index evolves in the same sense as the unemployment rate and the share of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The results of this study demonstrate that CSR motivates companies to identify the measures that can help them answer this question. Consistent with IJPHM 13,2 prior studies (Esmaeelinezhad and Boerhannoeddin, 2015;Khan et al, 2012), the findings of this study suggest that CSR implementation in pharmaceutical distribution companies can enhance internal processes, or, at the very least, modify existing organizational operations.…”
Section: Assessment Of the Measurement Model (Factor Analysis)supporting
confidence: 87%
See 1 more Smart Citation
“…The results of this study demonstrate that CSR motivates companies to identify the measures that can help them answer this question. Consistent with IJPHM 13,2 prior studies (Esmaeelinezhad and Boerhannoeddin, 2015;Khan et al, 2012), the findings of this study suggest that CSR implementation in pharmaceutical distribution companies can enhance internal processes, or, at the very least, modify existing organizational operations.…”
Section: Assessment Of the Measurement Model (Factor Analysis)supporting
confidence: 87%
“…This result is mainly due to the fact that financial performance alone cannot adequately capture a company's performance in today's competitive world. Indeed, a large number of studies have demonstrated that nonfinancial performance measures are more critical than financial measures in assessing a business' health and success, and that a firm's survivability is mainly associated with the mechanisms they apply to measure their non-financial performance, such as customer satisfaction and continuous improvement (Esmaeelinezhad and Boerhannoeddin, 2015;Robins, 2005). While financial perspective is a short-term measure, the other perspectives can be considered long-term measures.…”
Section: Assessment Of the Measurement Model (Factor Analysis)mentioning
confidence: 99%
“…Earlier scholars studied the impact of CSR on limited employee behaviors, like organizational citizenship behavior, organizational identification, and commitment (Abdullah & Rashid, 2012; Brammer et al, 2007; Lin, Lyau, Tsai, Chen, & Chiu, 2010). Limited studies have focused on EE which is a significant predictor of employee performance, productivity, and organizational performance, especially in developing countries like Pakistan (Esmaeelinezhad, Boerhannoeddin, & Singaravelloo, 2015; Gao et al, 2018; Glavas, 2016). According to Gao et al (2018), a very limited number of employees (13%) across the world are engaged and just the United States is facing a financial loss of around USD 500 billion yearly just because of the low productivity of disengaged workers.…”
Section: Discussionmentioning
confidence: 99%
“…Aguilera, et.al, (2007) stated that organizations alliedwith in total social responsibilities are accepted as fair organization.From the first hypothesis,it has found that companies CSR activities is influenced by philanthropic activities of an organization. Previous different studies have also foundthat philanthropic responsibilities have positive influenced on company's CSR (Esmaeelinezhad, Boerhannoeddin, and Singaravello, 2015;Lin, 2010;and Rego, Leal,Cunha,Faria, and Pinho, 2010). Based on these selected banks of Bangladesh, it is proved that companies have maintainedphilanthropic responsibilities for saving natural resources, caring for poverty alleviated people, making affiliation with nonprofit organization for development of education, health, culture and social development, and sports.…”
Section: Discussion Of the Findingsmentioning
confidence: 91%
“…But some researcher has found negative relationship between these two contracts. (Esmaeelinezhad, Boerhannoeddin, and Singaravello, 2015). In the perspective of Bangladesh, based on commercial banks' employees, it has positive impact on CSR.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%